The Problem of Mind in Contemporary Modern Discourse - Hanane, Lakli; Fatima, Ferhati (International Journal of Psychosocial Rehabilitation, 2022)
The clear intention of the critique of reason among most modern Arabs was to prove its historicity or historiography so that its meaning and ideological function could be revealed and standing on its borders as a prelude to cutting with it. Therefore, most of them have unanimously agreed to explain the crises and devastation inflicted on the Arab world in modern times by unhistoricity at the level of reason and undemocracy at the level of politics perhaps the biggest concern that has led them to build their own intellectual projects. However, may seem difficult to monitor the contours of optimism by giving firm foundations for reform in the Arab world due to the multiplicity of visions, which were quoted as models for discussing and resolving the crisis among some contemporary thinkers to keep the problematic about the possibility of reaching the choice of the optimal model to solve the crisis. So, the problem remains about the possibility of reaching choosing the optimal model for resolving the crisis according to a philosophical vision that seeks to reform reason in its Arab proposition and get out of the current.